Bali International Polytechnic Participation in Implementing the Sri Sedana Kerti Event in Jatiluwih Village - Marmaiyatno, marmaiyatno; Wahyuni, A. Nyoman Sri (Bina Nusantara University, 2024)
Community participation is very necessary in implementing the Sri Sedana Kerti Event in Jatiluwih Village. This community participation is related to being a committee in organizing the event, competition participants, Micro, Small and Medium Enterprises preparing culinary delights, and several stakeholders preparing souvenirs and supporting the implementation of the Sri Sedana Kerti event. One of those who participated in the implementation of the Sri Sedana Kerti event, namely the Convention and Event Management Study Program from the Bali International Polytechnic. The aim of this research is to analyze the participation of the Bali International Polytechnic in implementing the Sri Sedana Kerti event in Jatiluwih Village. This study used descriptive qualitative method. Data collection was carried out using observation techniques, in-depth interview techniques, and document study. The results of this research are the participation of the Bali International Polytechnic in implementing the Sri Sedana Kerti Event in Jatiluwih Village, namely organizing a Photo Contest, Tiktok Contest and Video Contest. Other PIB community service team participation, such as participation in the Grand Harvest, running competitions, hat decorating, music events and tent rental. The implementation of the event went smoothly, although there were problems that occurred due to the shift in the event date, which caused the cancellation of several telents, competitions and the awarding of competition prizes to be shifted as well. Keywords: Participation, Bali International Polytechnic, Event, Sri Sedana Kerti